2021
DOI: 10.3390/vaccines9020181
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Choline-Binding Proteins Involved in Virulence as Vaccine Candidates

Abstract: Streptococcus pneumoniae is a pathogen responsible for millions of deaths worldwide. Currently, the available vaccines for the prevention of S. pneumoniae infections are the 23-valent pneumococcal polysaccharide-based vaccine (PPV-23) and the pneumococcal conjugate vaccines (PCV10 and PCV13). These vaccines only cover some pneumococcal serotypes (up to 100 different serotypes have been identified) and are unable to protect against non-vaccine serotypes and non-encapsulated pneumococci. The emergence of antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 172 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…CBPs are especially interesting because many orthogonal approaches have unbiasedly reached the same conclusion: most CBPs contribute to bacterial virulence, and are immunogenic targets in human sera exposed to pneumococcal pneumonia ( Giefing et al., 2008 ). Recent advances have been made toward CBPs as candidate antigens in vaccine design as well as expanded knowledge on pathogenicity and virulence mechanisms ( Sempere et al., 2021 ). Here, we review CBPs that have shown contributions to Spn pathogenicity and are utilized in preclinical vaccine studies and clinical trial vaccine formulations.…”
Section: Choline-binding Proteins (Cbps)mentioning
confidence: 99%
“…CBPs are especially interesting because many orthogonal approaches have unbiasedly reached the same conclusion: most CBPs contribute to bacterial virulence, and are immunogenic targets in human sera exposed to pneumococcal pneumonia ( Giefing et al., 2008 ). Recent advances have been made toward CBPs as candidate antigens in vaccine design as well as expanded knowledge on pathogenicity and virulence mechanisms ( Sempere et al., 2021 ). Here, we review CBPs that have shown contributions to Spn pathogenicity and are utilized in preclinical vaccine studies and clinical trial vaccine formulations.…”
Section: Choline-binding Proteins (Cbps)mentioning
confidence: 99%
“…This concern overlaps the mosaic nature of PspA with regard to its ability to evade the host immune response and indicates that to avoid "PspA replacement" or emergence of a non-typable PspA version, any multi-valent PspA vaccine should be developed that covers conserved regions under both positive and negative pressure by the host (Yamaguchi et al, 2019). The risk of this can also be diminished by including more than one protein in any vaccine formulation, such as pneumolysin (Sempere et al, 2021).…”
Section: Potential Of Pspa As a Vaccine Antigenmentioning
confidence: 99%
“…The major concerns regarding the use of PspA in a pneumococcal vaccine stem from the lack of cross-reactivity between all the clades. Antibody against clades 1 and 2 are cross protective, however, cross protection is reduced with consideration to clades 3, 4, and 5 ( Sempere et al., 2021 ). This concern overlaps the mosaic nature of PspA with regard to its ability to evade the host immune response and indicates that to avoid “PspA replacement” or emergence of a non-typable PspA version, any multi-valent PspA vaccine should be developed that covers conserved regions under both positive and negative pressure by the host ( Yamaguchi et al., 2019 ).…”
Section: Potential Of Pspa As a Vaccine Antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…There has long been interest in and growing support for developing such a vaccine based on pneumococcal proteins. Pneumococcal proteins with vaccine potential have been extensively studied [ 13 ] and proposed as vaccine candidates based on their distribution among all capsule types and their ability to elicit protective immune responses against systemic infection in animal models. Such a vaccine would likely be immunogenic in young children, be less expensive to produce, and elicit strong immunological memory at least of the magnitude seen with conjugated CP.…”
mentioning
confidence: 99%